(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Glaucoma is One of the main causes of disability and blindness in the ICD – X class of Diseases of the eye and its appendage. Purpose. Study of the dynamics of primary and general disability due to glaucoma among the adult population of the Republic of Uzbekistan and Tashkent city for the period from 2010 to 2019. Material and Methods. A retrospective study of the data of the Medical and Social Service Agency under the Ministry of Health of the Republic of Uzbekistan from 2010 to 2019 on the number of disabled people among the adult population diagnosed with glaucoma in the Republic of Uzbekistan and Tashkent was realized. Intensive and extensive indicators, dynamics and structure of general and primary disability were calculated, average period indicators were determined, regressive analysis was accomplished and a forecast of the development of the situation for the coming years was given. Results. For the period from 2010 to 2019 years, 6842 people were recognized as disabled people in Uzbekistan for the first time in the Republic, while 58544 disabled people with this pathology were registered in the country during the study period. Of these, 57338 people (97.9±0.07%) individuals were with open-angle and closed-angle forms of glaucoma. During the study period, primary disability in glaucoma both in Uzbekistan and in Tashkent city has increased almost 2 times, the indicators of General disability are more stable, but also tend to increase. Conclusion. Analysis of the level and dynamic of primary and general disability due to glaucoma among the adult population of the Republic of Uzbekistan and Tashkent city for the period from 2010 to 2019 years showed a significant increase.